The Work of Erwin Rothbarth - Kalecki, M. (Review of Economic Studies, 1944)
Journal Article The Work of Erwin Rothbarth Get access M. Kalecki M. Kalecki Montreal Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 12, Issue 2, 1944, Pages 121–122, https://doi.org/10.2307/2296098 Published: 01 September 1944